URBANIZATION, URBAN DEVELOPMENT, AND PLANNING: NOAKHALI SADAR PERSPECTIVE - Israt Jahan Semu (SocioEdu: Sociological Education, 2025)
Urbanization and urban planning are both important for sustainable socio-economic development and nowadays urbanization has attracted the attention of various scholars. This paper aims to study the reasons for urbanization, urban planning, pattern and process of urbanization, urban governance, urban economic development, urban housing, urban transportation, urban land management and planning, infrastructure, urban poverty, and urban environment. This paper seeks a general understanding of urban development. Cities are considered a complex social fact because cities represent the future of global living. This paper tries to understand how economic factors are valuable behind urbanization. Rural-to-urban migration has happened widely in Bangladesh. There are push and pull factors of urbanization behind this migration. The study aims to outline the role of Pourashava, the people's work department, and non-government organizations that work for city planning and development. This study tries to find out the problems in slum areas their sufferings and social and economic exclusion. The main goal of my paper is to view the planned and balanced urban development across the Sadar, Noakhali.